Classical Antiquity and its Contribution to the Appreciation of Public Transportation - Diego Anhê Capel (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – The purpose of this work is to reflect on how Classical Architecture can contribute to enhancing urban Public Transportation in Birigui, São Paulo.Methodology – The method applied is the elaboration of an essay on this subject.Originality/Relevance – This work was developed by combining two themes: the Architecture produced in Classical Antiquity and Urban Mobility with its elements of Public Transportation.Results – The outcome is not exactly an applicable project, but propositions that lead the reader to a critical reflection on the subject.Theoretical/Methodological Contributions – The proposal is to provoke in the reader a reflection on the undervaluation of urban Public Transportation.Social and Environmental Contributions – How Urban Mobility can be regarded as something as valuable as the productions of Classical Antiquity.
Keywords: Classical Architecture; Urban Mobility; Public Transportation